Repurposing randomized, controlled, double-blinded homeopathic pathogenetic trial for determining the expiry of ultra-high diluted homeopathic drugs - Kurian Poruthukaren; Vivek Sakthidharan
Unlike conventional pharmaceuticals, ultra-high diluted homeopathic drugs lack measurable molecular content, posing challenges for scientific expiry determination. Currently, global regulatory agencies apply arbitrary expiry durations, risking either premature disposal or prolonged use beyond efficacy. We aimed to propose and test a scientifically valid method for determining the expiry of ultra-high diluted homeopathic drugs by repurposing randomized, double-blind, placebo-controlled pathogenetic trials. We conducted the trial using Allium cepa 30C, a drug with a well-documented pathogenetic profile. We randomly assigned thirty-six healthy volunteers to: freshly prepared Allium cepa - New Allium cepa, 16-year-old Allium cepa, and the placebo. Participants recorded symptoms over seven days. We extracted and analyzed the symptom elements (location, sensation, modality). We used Jaccard similarity indices to estimate trial noise. Statistical analyses included the Kruskal-Wallis test and post-hoc comparisons. We calculated the effect size using epsilon squared. The New Allium cepa group showed the highest symptom production. The old Allium cepa group demonstrated a 59.61% reduction in pathogenetic ability compared to the New Allium cepa. While the difference was insignificant (p = 0.108), a large effect size ((Sfp2 (B= 0.193) indicated a potentially meaningful difference. Placebo had the fewest responses and symptom elements. We propose that the repurposed homeopathic pathogenetic trials provide a scientific, reproducible model to assess the expiry of ultra-high diluted homeopathic drugs. This novel approach may aid in developing global regulatory standards and enhance the reliability of homoeopathic practice.s